Ichthyosis with confetti caused by new and recurrent mutations in KRT10 associated with varying degrees of keratin 10 mis-localization. Issue 1 (April 2020) - Pan, Yuxue; Feng, Cheng; Wang, Huijun; Lee, Mingyang; Tang, Zhanli; Lin, Zhimiao
Highlights: We present 5 cases with of IWC-I with different KRT10 mutations, two of which are located close to K10 tail, causing minor substitution of arginine. The level of K10 nuclear mis-localization may correlate with the number of arginine residues in the mutant K10 tail in IWC-I. The level of K10 nuclear mis-localization and the number of arginine residues seem less or not related to the number of pale spots of IWC phenotype. Abstract: Background: Ichthyosis with confetti (IWC) is an extremely rare autosomal-dominant genodermatosis characterized by erythroderma with numerous confetti-like pale spots. IWC is caused by mutations in KRT10 (IWC-I) or KRT1 (IWC-II) which affect their tail domains. In IWC-I, the mutations lead to replacement of glycine/serine-rich keratin 10 (K10) tail with arginine- or alanine-rich frameshift motifs, causing K10 mis-localization which might trigger loss of the mutant KRT10 allele via mitotic recombination, leading to genetic reversion. Objective: To investigate mutations in five IWC-I patients and their functional consequences. Methods: We performed Sanger sequencing of KRT1 and KRT10 in peripheral blood samples of five patients, with highly polymorphic KRT10 SNPs genotyped to confirm loss-of-heterozygosity in the epidermis of pale spots. K10 expression pattern was examined in both patient skin biopsies and HaCaT cells overexpressing mutant KRT10- enhanced green fluorescence protein fusion. Results: Four novel and one recurrent KRT10 mutations were identified in patient peripheral blood samples but not in the corresponding pale spot epidermis. Two of the mutations, c.1696_1699dupCACA and c.1676dupG, affected residues close to K10 carboxyl terminus and encoded only 3 and 6 arginine residues, which were far fewer than reported previously. Interestingly, imaging analyses for K10 in HaCaT cells overexpressing either of these two mutations and in the corresponding patients' affected skin, showed a remarkably lower level of K10 mis-localization compared to that of other mutations reported in this study. Conclusions: Our findings suggest that the number of arginine residues in the mutant tail may correlate with the level of K10 mis-localization in IWC-I keratinocytes. These results expand the genotypic and phenotypic spectrum of IWC-I.